Quality Evaluation of Yoghurt Supplemented with Carrot Juice- - Sulieman, Abdel Moneim E.; Abdelrahman, Mushiera M.; Elkhalifa, Elamin A. (Gezira Journal of Engineering and Applied Sciences; Vol 6 No 1 (2011), 2018)
In the present study, carrot juice was used in the preparation of yoghurt using cow's milk. The effect of refrigerated storage (6°C) in the chemical and microbiological characteristics of yoghurt samples was investigated during 1, 7 and 15 days of storage. The chemical analyses showed that the moisture content was 88 ± 0.4% in control yoghurt in day 1 which was lower than those of carrot yoghurt samples which ranged between 89 ± 0.5% and 93 ± 0.6%. The protein content of control yoghurt (A), yoghurt supplemented with 5% carrot juice (B 1 ), yoghurt supplemented with 10% carrot juice (B 2 ) and yoghurt supplemented with 15% carrot juice (B 3 ) was 4 ± 0.06%, 3.9 ± 0.02%, 3.9 ± 0.01% and 3.8 ± 0.02%, respectively. The ash content of carrot yoghurt samples ranged between 0.45 ± 0.004% and 0.6 ± 0.07%. The total solids content was 12 ± 0.7% in control yoghurt at day 1 which was higher than those of carrot yoghurt samples (11 ± 0.3% and 7 ± 0.6%). However, the total solids content of carrot yoghurt decreased during storage.  The acidity (expressed as lactic acid %) increased progressively during storage of all yoghurt samples while the pH decreased. The microbiological analyses revealed entire absence of coliform bacteria during storage; however, few numbers of yeasts were detected in the control yoghurt. On the other hand, the total count of bacteria in control yoghurt was 3.3 x 10 4 c.f.u/ml at day 1 increased in carrot yoghurt samples to the range 3.5 x 10 4 - 4 x 10 4 c.f.u/ml. Also lactic acid bacteria increased in all yoghurt samples. The sensory evaluation indicated acceptance of all yoghurt samples, with preference to the yoghurt prepared using 5% carrot juice, especially in its colour, texture and flavour.